The Toll-Like Receptor 2 agonist PEG-Pam2Cys as an immunochemoprophylactic and immunochemotherapeutic against the liver and transmission stages of malaria parasites. Issue 3 (December 2018) - Ernest, Medard; Hunja, Carol; Arakura, Yuka; Haraga, Yohei; Abkallo, Hussein M.; Zeng, Weiguang; Jackson, David C.; Chua, Brendon; Culleton, Richard
Abstract: Both vaccine and therapeutic approaches to malaria are based on conventional paradigms; whole organism or single antigen epitope-based vaccines administered with or without an adjuvant, and chemotherapeutics (anti-malaria drugs) that are toxic to the parasite. Two major problems that limit the effectiveness of these approaches are i) high levels of antigenic variation within parasite populations rendering vaccination efficacy against all variants difficult, and ii) the capacity of the parasite to quickly evolve resistance to drugs. We describe a new approach to both protection from and treatment of malaria parasites that involves the direct stimulation of the host innate immune response through the administration of a Toll-Like Receptor-2 (TLR2) agonist. The activity of PEG-Pam2 Cys against the hepatocytic stages, erythrocytic stages and gametocytes of the rodent malaria parasite Plasmodium yoelii was investigated in laboratory mice. We show that administration of PEG-Pam2 Cys, a soluble form of the TLR2 agonist S-[2, 3-bis(palmitoyloxy)propyl] cysteine (Pam2 Cys), significantly and dramatically reduces the numbers of malaria parasites that grow in the livers of mice following subsequent challenge with sporozoites. We also show that treatment can also clear parasites from the liver when administered subsequent to the establishment of infection. Finally, PEG-Pam2 Cys can reduce the numbers of mosquitoes that are infected, and the intensity of their infection, following blood feeding on gametocytaemic mice. These results suggest that this compound could represent a novel liver stage anti-malarial that can be used both for the clearance of parasites following exposure and for the prevention of the establishment of infection. Graphical abstract: Image 1 Highlights: TLR-2 agonist Pam2 Cys reduces malaria parasite burden in the liver when administered prior to sporozoite challenge. It also reduces malaria parasite burden in the liver when administered 24 h after sporozoite challenge. It reduces the transmissibility of a malaria infection to mosquitoes.